The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1986
DOI: 10.1017/s0022112086001118
|View full text |Cite
|
Sign up to set email alerts
|

An experimental study of transient effects in the breakup of viscous drops

Abstract: A computer-controlled four-roll mill is used to examine two transient modes of deformation of a liquid drop: elongation in a steady flow and interfacial-tensiondriven motion which occurs after the flow is stopped abruptly. For modest extensions, drop breakup does not occur with the flow on, but may occur following cessation of the flow as a result of deterministic motions associated with internal pressure gradients established by capillary forces. These relaxation and breakup phenomena depend on the initial dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

34
233
1
1

Year Published

1990
1990
2017
2017

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 395 publications
(273 citation statements)
references
References 27 publications
34
233
1
1
Order By: Relevance
“…Subsequently, the droplet attains a dumbbell-like shape before becoming an ellipsoid. This type of relaxation, consisting of an initial relaxation by means of a shape change without significant reduction of the droplet length, followed by a simple droplet retraction, was reported on by several authors (Stone et al (1986) (2009)). In those studies, the highly deformed non-ellipsoidal droplet shape was however generated by applying flow with a supercritical Ca rather than confining the droplet between parallel plates.…”
supporting
confidence: 55%
“…Subsequently, the droplet attains a dumbbell-like shape before becoming an ellipsoid. This type of relaxation, consisting of an initial relaxation by means of a shape change without significant reduction of the droplet length, followed by a simple droplet retraction, was reported on by several authors (Stone et al (1986) (2009)). In those studies, the highly deformed non-ellipsoidal droplet shape was however generated by applying flow with a supercritical Ca rather than confining the droplet between parallel plates.…”
supporting
confidence: 55%
“…The viscosity ratios we tested ( 1.5 to 4.1) may not vary enough to have an impact on ⁄ . For a free drop submitted to shear, Stone et al 28 found that breakup occurs above a critical elongation ratio, function of but for 0.1 to 1, the critical elongation ratio did not vary significantly. Similarly, we find Oh from 1.7×10 -2 to 5.3×10 -2 .…”
Section: B Critical Elongation Ratiomentioning
confidence: 99%
“…Several methods to investigate the droplet deformation and break-up under laminar conditions are established, experimentally e.g., in a four-roller mill [16,[51][52][53][54][55][56][57] or by modelling and numerical simulation [56,[58][59][60][61], respectively. Analysing the resulting DSD as a function of deforming stresses and material properties, especially viscosity ratio, allowed several authors to correlate the droplet break-up with the dimensionless Capillary number Ca.…”
Section: Why Do We Need Detailed Information On the Hph Process?mentioning
confidence: 99%